Managing hazards, reducing risks and increasing investments in agriculture – some perspectives: critical analysis of policy issues for repositioning agriculture in the Caribbean - Inter-American Institute for Cooperation on Agriculture; Technical Centre for Agricultural and Rural Cooperation (Inter-American Institute for Cooperation on Agriculture, 2006)
This Special paper seeks to widen understanding and promote a new mindset with respect to three issues critical to the agriculture development process.